Mengupas Pengaruh E-Wom pada Niat Beli Produk Somethinc di Kalangan Gen Z Surakarta: Peran Kualitas dan Nilai yang Dirasakan - Arini Larasati Moqhtar Putri; Liana Mangifera (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research is essential to understanding the influence of electronic communication on Generation Z’s purchasing decisions for beauty products. The study aims to analyze the impact of Electronic Word of Mouth (E-WOM) on the purchase intention of Generation Z in Surakarta, individuals born between 1997 and 2012, specifically for Somethinc products. A quantitative approach was employed, with data collected through questionnaires distributed to 147 respondents. The data was analyzed using multiple linear regression with the help of SmartPLS. The findings indicate that perceived quality is positively influenced by the quantity of E-WOM, while perceived value is not significantly affected. Both perceived quality and perceived value act as mediators in the research model. Meanwhile, the quality and valence of E-WOM significantly and positively affect both variables as well as purchase intention. Perceived quality is proven to mediate the relationship between E-WOM and purchase intention, whereas perceived value does not function as a mediator. These findings suggest that improving the quality and valence of E-WOM can enhance trust and purchase intention among Generation Z. However, the study has limitations regarding the perceived value variable, which does not serve as a mediator, and the limited availability of relevant journal sources. Future research is encouraged to expand the sample scope and deepen the analysis of the perceived value variable to achieve more comprehensive results.